1983
DOI: 10.1164/arrd.1983.127.5.559
|View full text |Cite
|
Sign up to set email alerts
|

Rapid Diagnosis of Legionnaires’ Disease by Latex Agglutination1,2

Abstract: We developed a latex agglutination test to detect antigen(s) of serogroup 1 Legionella pneumophila in urine and evaluated its ability to diagnose legionnaires' disease. Antigen was detected in 46, or 70%, of 66 patients with serogroup 1 legionnaires' disease but in none of 51 patients with various bacteremic infections nor 60 with urinary tract infections. One of 50 patients with other pulmonary infections was antigen-positive, an immunosuppressed patient with Pneumocystis carinii infection. Seven other patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
1
1

Year Published

1984
1984
2014
2014

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(13 citation statements)
references
References 18 publications
0
11
1
1
Order By: Relevance
“…Plates often require at least 5-7 days before Legionella colonies become visible, at which point the density of competing organisms often either renders enumeration infeasible or completely obscures the surface of culture plates (Bopp et al, 1981, Leoni & Legnani, 2001. Once Legionella colonies are visible, their positive identification is often primarily visual and/or confirmed by latex agglutination (Sathapatayavongs et al, 1983). However, these methods in their own right present limitations, as noted by Carvalho et al (2007) who demonstrated that from 20 colonies presenting the characteristic Legionella ''ground glass'' 14/20 (70%) were positive for L. pneumophila.…”
Section: Detection Of Legionella By Culture Methodsmentioning
confidence: 99%
“…Plates often require at least 5-7 days before Legionella colonies become visible, at which point the density of competing organisms often either renders enumeration infeasible or completely obscures the surface of culture plates (Bopp et al, 1981, Leoni & Legnani, 2001. Once Legionella colonies are visible, their positive identification is often primarily visual and/or confirmed by latex agglutination (Sathapatayavongs et al, 1983). However, these methods in their own right present limitations, as noted by Carvalho et al (2007) who demonstrated that from 20 colonies presenting the characteristic Legionella ''ground glass'' 14/20 (70%) were positive for L. pneumophila.…”
Section: Detection Of Legionella By Culture Methodsmentioning
confidence: 99%
“…Detection of Legionella antigen in urine has also been accomplished by radioimmunoassay, enzyme immunoassay, and latex agglutination (227). The (75,269), and the specificity approaches 100% (269).…”
Section: Culturementioning
confidence: 99%
“…Approximately 80% of patients with serogroup 1 Legionella pneumophila pneumonia excrete detectable levels of an antigen, presumably derived from the organism, in their urine (7). Assays developed to detect this antigen appear to be highly specific, yielding positive results only in patients with legionellosis (7,9,13,14). To be optimally useful as diagnostic tools for physicians making therapeutic decisions, these assays must detect antigen early in the course of the illness.…”
mentioning
confidence: 99%